Feasibility study on estimation of rice weevil quantity in rice stock using near-infrared spectroscopy technique - Puttinun Jarruwat; Prasan Choomjaihan (My University, 2013)
Thai rice is favored by large numbers of consumers of all continents because of its excellent taste, fragrant aroma and fine texture. Among all Thai rice varieties, Thai Hommali rice is the most preferred. Classification of rice as premium quality requires that almost all grain kernels of the rice be perfectly whole with only a small quantity of foreign particles. Of all the foreign particles found in rice, rice weevils can wreck severest havoc on the quality and quantity of rice such that premium grade rice is transformed into low grade rice. It is widely known that rice millers adopt the "overdose" fumigation practice to control the birth and propagation of rice weevils, the practice of which inevitably gives rise to pesticide residues on rice which end up in the body of consumers. However, if population concentration of rice weevils could be approximated, right amounts of chemicals for fumigation would be applied and thereby no overdose is required. The objective of this study is thus to estimate the quantity of rice weevils in both milled rice and brown rice of Thai Hommali rice variety using the near infrared spectroscopy (NIRS) technique. Fourier transforms near infrared (FT-NIR) spectrometer was used in this research and the near-infrared wavelength range was 780–2500 nm. A total of 20 levels of rice weevil infestation with an increment of 10 from 10 to 200 mature rice weevils were applied to 1680 rice samples. The spectral data and quantity of weevils are analyzed by partial least square regression (PLSR) to establish the model for prediction. The results show that the model is able to estimate the quantity of weevils in milled Hommali rice and brown Hommali rice with high [Formula: see text] of 0.96 and 0.90, high RPD of 6.07 and 3.26 and small bias of 2.93 and 2.94, respectively.
Keywords: Rice weevil; Paddy field; Brown rice; Spectroscopy and Chemometric Analyses